PENGARUH KADAR GULA TERHADAP KUALITAS SELAI DAUN BINAHONG - Anggraini, Rinella; Faridah, Anni; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This research wasconstituted by utilization of the leaves of binahong in food processing is still lacking. Leaves binahong have good properties for the body. The research purpose to analyze effect of sugar content as much as 62,5%, 75% and 87,5 to the quality of jam in terms of color, aroma, texture and taste. The type of this study was pure experiments (true experiment), using a completely randomized single-factor design method. Data in used areprimer data obtained from 30 semi-trained panelists who provide answers from the questionnaire (organoleptic test format). The obtained data has been tabulated and variant analysis (ANAVA) is performed. If different proceed with Duncan test. The results showed that there was an effect of 87,5% sugar treatment for the color of dark green color, the aroma was quite fragrant cinnamon and quite typical of binahong leaf, the texture is quite smooth and quite easy to be applied and the quality of sweet taste and quite typical of binahong leaf.Keywords: Sugar Level, Binahong Leaves, Jam, Quality.